INVESTIGATION OF TEMPERATURE IN ORTHOPAEDIC DRILLING USING RESPONSE SURFACE METHODOLOGY (Pakistan Journal of Science, 2016)
Rise in temperature is inevitable in orthopaedic drilling. Massive research had been done in the field of orthopaedic drilling to investigate the effect of cutting conditions, bone related parameters, and drill bit geometric parameters on heat generation and minimum surrounding tissues injury. In present research, contradictory conclusions regarding the cutting conditions and drill bit geometric parameters were observed. Minimum temperature of 31°C was achieved at speed of 186 rpm, feed of 0.196 mm/rev, drill diameter of 3.85mm, and drill tip angle of 110°. Response Surface Methodology (RSM) was used to develop a mathematical model to predict the type of relationship between inputs and response. It was concluded that the most influencing parameter was drill diameter.
Keywords: Temperature; Orthopaedic drilling; Drill parameters; Response surface methodology